Serum FGF23 and DPP4 Levels as Biomarkers for Coronary Artery Disease Severity in Type 2 Diabetic Patients with Coronary Heart Disease - Zhong X; Liang Z; Liao H; Zhan Y; Li G; Wu H; Li J (International Journal of General Medicine)
Xuanli Zhong, Zhanyun Liang, Haiming Liao, Yuanyuan Zhan, Ge Li, Huanping Wu, Jinying Li Department of Endocrinology, The Affiliated Shunde Hospital of Jinan University, Foshan, Guangdong, 528300, People’s Republic of ChinaCorrespondence: Jinying Li, Department of Endocrinology, The Affiliated Shunde Hospital of Jinan University, No. 50 Guizhou Avenue East, Ronggui Street, Foshan, Guangdong, 528300, People’s Republic of China, Tel +8613823406301, Email liwu3435378q@sina.comObjective: This study aimed to evaluate the relationship between serum fibroblast growth factor 23 (FGF23) and dipeptidyl peptidase 4 (DPP4) levels, and the severity and prognosis of coronary artery disease (CAD) in patients with type 2 diabetes mellitus (T2DM) and coronary heart disease (CHD).Methods: A total of 113 patients with both T2DM and CHD (T2DM+CHD group) and 74 patients with T2DM without CHD (T2DM-only group) who underwent coronary angiography between January 2021 and June 2023 were enrolled. Based on Gensini scores, the T2DM+CHD group was further divided into three subgroups: mild (n=38), moderate (n=46), and severe (n=29) lesions. Serum levels of FGF23 and DPP4 were determined using enzyme-linked immunosorbent assay (ELISA). Correlation analysis and logistic regression were conducted to assess the association between biomarker levels and both disease severity and prognosis. Receiver operating characteristic (ROC) curve analysis was used to evaluate the predictive value of these biomarkers.Results: Serum levels of FGF23 and DPP4 were significantly higher in the T2DM+CHD group than in the T2DM-only group (P< 0.05), and increased progressively with the severity of CAD (P< 0.05). A positive correlation was observed between the levels of these biomarkers and CAD severity (r=0.714 for FGF23; r=0.437 for DPP4; P< 0.05). Patients with poor prognosis exhibited increased left atrial diameter (LAD) and biomarker levels, along with reduced left ventricular ejection fraction (LVEF) (P< 0.05). Multivariate analysis identified increased LAD, moderate-to-severe CAD, and elevated levels of FGF23/DPP4 as independent risk factors for poor prognosis, while higher LVEF served as a protective factor (P< 0.05). Moreover, a combined predictive model using both FGF23 and DPP4 demonstrated superior diagnostic performance (AUC=0.921; P< 0.05) compared to the use of each biomarker individually.Conclusion: Elevated serum levels of FGF23 and DPP4 are significantly associated with both the severity and poor prognosis of CAD in patients with T2DM and CHD. These findings suggest that FGF23 and DPP4 may serve as valuable biomarkers for risk stratification and clinical decision-making in this patient population.Keywords: diabetes mellitus, Coronary heart disease, coronary artery disease, prognosis, fibroblast growth factor 23, dipeptidyl peptidase-4